Spectacle scan / Nur Aqilah Kamaruddin, Siti Shaheera Sainuri and Nurshafiqah Ruslan Rashid - Kamaruddin, Nur Aqilah; Sainuri, Siti Shaheera; Ruslan Rashid, Nurshafiqah (2018)
The product invented is Spectacle Scan. This product is an alternative to a convenient scanner that could connect to portable printer. The unique of this product is the usage of 'Spectacle Scan' that none of the existing products in the market have. It can simply scan all the information or what you need to print easily.